2018
DOI: 10.1016/j.freeradbiomed.2018.04.583
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 2 prevents the development of heart failure

Abstract: Our study suggests a cardioprotective role for PON2 in both experimental and human heart failure, which may be associated with the ability of PON2 to improve mitochondrial function and diminish ROS generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In addition to the overall high OXPHOS scores, the stem-like signature was associated with enhanced expression of OXR1 and PON2 . Being essential for protection against oxidative stress, these genes may counteract higher reactive oxygen species (ROS) levels resulting from enhanced OXPHOS rates [ 34 , 35 ]. Another gene included in the stem-like signature is MAP2K6 —an essential p38 signaling component [ 36 ] known to be associated with high OXPHOS levels in intestinal stem cells [ 23 ] ( Figure S1f , Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the overall high OXPHOS scores, the stem-like signature was associated with enhanced expression of OXR1 and PON2 . Being essential for protection against oxidative stress, these genes may counteract higher reactive oxygen species (ROS) levels resulting from enhanced OXPHOS rates [ 34 , 35 ]. Another gene included in the stem-like signature is MAP2K6 —an essential p38 signaling component [ 36 ] known to be associated with high OXPHOS levels in intestinal stem cells [ 23 ] ( Figure S1f , Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From 2010 it was highlighted PON2's ability to reduce oxidative stress in mitochondria and to prevent apoptosis in the endoplasmic reticulum [1-4] with a still unclarified mechanism suggested to be independent from the lactonase activity [1]. From here on scientists explored PON2 antioxidant effects, its role in preventing heart failure [5] and its involvement in any type of tumor [6].…”
Section: Introductionmentioning
confidence: 99%
“…As for PON1, we show for the first time that injection of rePON1 to mice decreases aortic cholesterol and TAG contents. Although PON1 is associated with HDL in the circulation, PON2 is expressed in various major organs as an intracellular enzyme, and is known for its atheroprotective and cardioprotective roles (Li et al, ; Ng et al, ; Rom and Aviram, ). Here, we found that rePON1 injection upregulated PON2 in the aorta, whereas both PJ consumption and rePON1 injection reduced Dgat1 expression, the key enzyme that catalyzes the final step in TAG biosynthesis by attaching a long‐chain fatty acyl‐CoA to diacylglycerol (Yen et al, ).…”
Section: Discussionmentioning
confidence: 99%